Dialysis-dependant patients’ outcomes during coronavirus-19 hospitalization early vs. Late survival - Kusic Milicevic, Jovana; Karapandzic, Marija; Stajcic, Mina; Dodic, Jelena; Andjelkovic Apostolovic, Marija; Apostolovic, Branislav; Markovic, Rodoljub; Djurkovic, Veselinka; Momcilovic-Zivkovic, Danijela; Jordanova, Elena; Indjic, Djordje; Komadina, Ljiljana; et al. (Medical Research, 2025)
INTRODUCTION: During the COVID-19 pandemic, receiving hemodialysis was recognized as a predictor of poor survival. This study evaluated in-hospital and late survival in patients treated with hemodialysis during COVID-19 hospitalization. METHODS: This single-center retrospective study included 176 patients requiring hemodialysis during COVID-19 hospitalization. Patients were divided into three groups: acute kidney injury (AKI), acute-on-chronic kidney disease (aCKD), and chronic hemodialysis (HD). Data was collected from patients’ electronic records. RESULTS: The majority (73.3%) of the study population were chronic hemodialysis patients. The overall in-hospital mortality was high (35.8%), and differed significantly among groups: 82.1%, 57.9% and 22.5% in the AKI, aCKD, and HD patients, respectively (p<0.001). After 12 months, death occurred in almost 30% of the reached patients, of whom the majority were from the chronic hemodialysis group. CONCLUSION: Dialysis-dependent patients experience high mortality during COVID-19, especially those who develop AKI and aCKD. Chronic hemodialysis patients are exposed to better in-hospital survival; however, their one-year mortality remains significant. Keywords: COVID-19, acute kidney injury, chronic kidney disease, exacerbation of chronic kidney disease, hemodialysis